A Strategy for Separating and Recycling Solid Catalysts Based on the pH‐Triggered Pickering‐Emulsion Inversion1. Issue 29 (7th June 2013) - Yang, Hengquan; Zhou, Ting; Zhang, Wenjuan
<x xml:space="preserve">Abstract</x> Turn you inside out: A novel method for performing in situ separation and recycling of submicrometer‐sized solid catalysts is developed based on the pH‐triggered inversion of Pickering emulsions (see scheme; o=oil, w=water). Solid catalysts can be recycled 36 times without significant loss of activity. The method differs from conventional methods in terms of speed, energy consumption, catalyst separation, and recycling effectiveness.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>